Study on Application and Benefits of Technology in Agricultural Marketing: Exploring the Effective Use of Technology in Agricultural Marketing for Sustainable Productivity and Employability (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In order to accelerate the productivity and employability of individuals, agriculture requires successful technological use. The key aim of this paper is to explain how developments in the agricultural sector can be used effectively. Many kinds of technology are used to increase efficiency. Types of technology, the importance of agricultural technology, the use of technology for agricultural markets, the benefits of technology in agriculture are the major fields taken into consideration. The use of technologies will improve the sustainability of farmers' livelihoods.